(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
The growing body of publications on the synthesis of 1,3-diazine-bridged systems has drawn increasing attention to these compounds. The aim of our work was to synthesise novel bisazomethines derived from 4,6-dihydroxy-2-methylpyrimidine-5-carbaldehyde (1). A series of Schiff bases was obtained via nucleophilic addition of aliphatic diamines to the carbonyl group of substrate1. Water was employed as the sole solvent during synthesis, affording target products in 8590% isolated yields. Structural confirmation was achieved by H and C nuclear magnetic resonance (NMR) spectroscopy. In silico screening (PASS Online, CLC-pred, Antivir-pred, and GUSAR Online) revealed that the synthesised bisazomethines exhibit broad-spectrum bioactivity, including antihypertensive, antibacterial, and anticancer properties, while maintaining Class 4 toxicity (low risk). Thus, we report novel bridged bisazomethines based on a 5-formyl derivative of 2-methylpyrimidine-4,6-diol, which combine a promising safety profile with multifaceted biological activity.